2016
DOI: 10.1242/jeb.141150
|View full text |Cite
|
Sign up to set email alerts
|

To crash or not to crash: how do hoverflies cope with free-fall situations and weightlessness?

Abstract: Insects' aptitude to perform hovering, automatic landing and tracking tasks involves accurately controlling their head and body roll and pitch movements, but how this attitude control depends on an internal estimation of gravity orientation is still an open question. Gravity perception in flying insects has mainly been studied in terms of grounded animals' tactile orientation responses, but it has not yet been established whether hoverflies use gravity perception cues to detect a nearly weightless state at an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 47 publications
4
24
0
Order By: Relevance
“…As observed previously [4], hoverflies subjected to free falls initiated their flight after approximately 100 ms in both uniform and contrasting wall texture conditions (p ¼ 0.12; F ¼ 2.4727; figure 2a). However, top lighting conditions significantly decreased the reaction wingbeat triggering) times ( p , 0.01; F ¼ 9.4352).…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…As observed previously [4], hoverflies subjected to free falls initiated their flight after approximately 100 ms in both uniform and contrasting wall texture conditions (p ¼ 0.12; F ¼ 2.4727; figure 2a). However, top lighting conditions significantly decreased the reaction wingbeat triggering) times ( p , 0.01; F ¼ 9.4352).…”
Section: Resultssupporting
confidence: 79%
“…This reflex, which is known as the dorsal light response (DLR), has also been described in detail in fish [2]. The importance of the orientation of an artificial horizon in blowflies' head roll orientation processes has also been previously established, as well as the fact that these insects probably do not use gravity information to perform this task [3], which has been assessed in freely flying hoverflies based on free fall experiments [4], contrary to the well-known negative gravitaxy behaviour observed in walking Drosophila [5,6]. These results suggest that visual processes predominate over gravity-based ones in the strategies used by flying flies to stabilize their flight, and support the idea that there exists some kind of vertical reference frame in flies' brains based on the DLR.…”
Section: Introductionmentioning
confidence: 99%
“…A common perturbation for both flight and walking is a free fall. Flies use vision to guide landing when dropped from a 40 cm height (Goulard et al, 2016), but in a shorter fall, vision may not be sufficiently fast.…”
Section: Introductionmentioning
confidence: 99%
“…When resting on a surface, the force of gravity is equal and opposite to ground reaction forces at the legs. Should the legs detach, the will body accelerate at a rate determined by F=ma, where the force is mg, and thus the acceleration will be equal to the gravitational constant g. The fly could detect the fall by sensing (1) changing leg loads (Zill et al, 1992), (2) increasing visual flow (Goulard et al, 2016(Goulard et al, , 2018 or (3) inertial body forces. Inertial body forces (fictitious or d'Alembert forces) act on accelerating masses; for example, causing a person to feel a sideways pull on a spinning fairground ride.…”
Section: Introductionmentioning
confidence: 99%
“…As a third control feedback loop, an active system of reorientation based on a quasi-panoramic eye constantly realigned its gaze parallel to the nearest surface followed: BeeRotor demonstrated its abilities and achieved automatic terrain-following despite steep reliefs ( Figure 8) without a need for inertial frames to access the verticality as flying insects do. Indeed, behavioral experiments performed 35 years ago on flying insects in zero gravity [129] or recent behavioral experiments with hymenopterans [37] or dipterans [130] demonstrated that flying insects do not actually sense verticality in flight by means of gravity perception as vertebrates do. The eye reorientation therefore enables BeeRotor, at an earlier stage, to detect the increase in the optic flow due to steep relief in order to properly avoid the obstacle [11].…”
Section: Obstacle Avoidance In the Vertical Planementioning
confidence: 99%